Bulk Purification and Deposition Methods for Selective Enrichment in High Aspect Ratio Single-Walled Carbon Nanotubes. - Bhatt, Nidhi P.; Vichchulada, Pornnipa; Lay, Marcus D. (Journal of the American Chemical Society, 2012)
Aqueous batch processing methods for the concurrent purification of single-walled carbon nanotube (SWNT) soot and enrichment in high aspect ratio nanotubes are essential to their use in a wide variety of electronic, structural, and mechanical applications. This manuscript presents a new route to the bulk purification and enrichment of unbundled SWNTs having average lengths in excess of 2 ~m. Iterative centrifugation cycles at low centripetal force not only removed amorphous C and catalyst nanopartides but also allowed the enhanced buoyancy of surfactant encapsulated, unbundled, high aspect ratio SWNTs to be used to isolate them in the supernatant. UV-vis-NIR and Raman spectroscopy were used to verify the removal of residual impurities from as-produced (AP-grade) arc discharge soot and the simultaneous enrichment in unbundled, undamaged, high aspect ratio SWNTs. The laminar flow deposition process (LFD) used to form two- dimensional networks of SWNTs prevented bundle formation during network growth. Additionally, it further enhanced the quality of deposits by taking advantage of the inverse relationship between the translational diffusion coefficient and length for suspended nanoparticles. This resulted in preferential deposition of pristine, unbundled, high aspect ratio SWNTs over residual impurities, as observed by Raman spectroscopy and atomic force microscopy (AFM).